PROFESIONALISME GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADARSAH IBTIDAIYAH TAHFIDZ AL-ASYHAR MALANG - Zumrotul Faizah; Muhammad Hanief; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakThis study aims to find out about the professionalism of teachers in the Madrasah Ibtidaiyah Tahfidz Al asyhar Malang in improving the quality of education. this research was conducted using data collection techniques namely observation, interviews, and documentation. In this study researchers used interview instruments which were arranged to get the results of interviews. Teacher professionalism is a condition that aims to provide quality in authority in the field of education and teaching the essence of the profession being a teacher is a job that grows because of work that requires stages in taking college in teacher training. Therefore professional teachers are jobs or tasks carried out with the task of educating, teaching, guiding, directing, training, evaluating, and evaluating their students with their best abilities. In this case the researcher will discuss the teacher professionalism in improving the quality of education in the Madfah Ibtidaiyah Tahfidz Al asyhar Malang. Keywords: Teacher professionalism, quality of education